KEPENTINGAN RUSIA DALAM BIDANG MARITIM DI INDONESIA - Hamid, Fadra; Larasati, Ayu (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This study aims to analyze the investment of European countries, especially Russia, in the maritime sector in Indonesia. This research will focus on Russia's economic and political interests in the maritime sector in Indonesia. The results of the research obtained are that in general Russia has not developed a type of maritime sector cooperation with Indonesia as large as other European countries. Russia-Indonesia maritime cooperation is still limited to the defense and packing industries. While other European countries are already engaged in the energy, fishery, technology and service industries. European countries understand the importance of Indonesia's maritime strategic position. For Russia, Indonesian territory has never been a political interest, but rather a partner of economic cooperation.